F(x)=-5t^2+20t+60
Divide everything by -5
f(x)=t^2-4t-12
(t-6)(t+2)
Set it up to zero
t-6=0. t+2=0
t=6. t=-2
Since you can’t have negative seconds, the answer is 6 seconds
So first you plug 6 into the equation which is 4(6)-10.
Using PEMDAS, you solve what’s in the parenthesis first and you get 24-10.
24-10=14
f(6)=14
Answer:
Step-by-step explanation:
Take the natural logarithm of both sides of the equation to remove the variable from the exponent.
ln
(
6
x
)
=
ln
(
66
)
Expand
ln
(
6
x
)
by moving
x
outside the logarithm.
x
ln
(
6
)
=
ln
(
66
)
Divide each term by
ln
(
6
)
and simplify.
Tap for more steps...
x
=
ln
(
66
)
ln
(
6
)
The result can be shown in multiple forms.
Exact Form:
x
=
ln
(
66
)
ln
(
6
)
Decimal Form:
x
=
2.33829083
…
What three consecutive integers have a sum of 48? Which means that the first number is 15, the second number is 15 + 1 and the third number is 15 + 2. Therefore, three consecutive integers that add up to 48 are 15, 16, and 17.